ANALISIS AKTIVITAS BELAJAR BIOLOGI SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR KELAS VII SMP NEGERI 3 RAMBAH SAMO TAHUN PEMBELAJARAN 2014/2015 - -, Hoirina; Afifah, Nurul; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
The study aims of to knowing the activity in study of biology in VII grade in SMP N 3 Rambah Samo. Type of this research is deskriptive. The subject in this research is VII grade student in second semester SMP N 3 Rambah Samo academic years 2014/2015. Technique of colleching the data use analysis data with observation sheet. The result from all the persentase was got. Student aktivitywith tecnique picture in class VII SMP N 3 Rambah Samo is 72,93% with criteria good enough.